Riboflavin content in selected traditional foods from Black Sea Area countries - Costa, H.S. (2012)
Riboflavin (vitamin B2) is an essential water-soluble vitamin present in a wide variety of foods, namely in milk, dairy products, cereal products, meat products and green leafy vegetables. The primary form of the vitamin is an integral component of the coenzymes flavin mononucleotide and flavin-adenine dinucleotide. It is in these bound coenzyme forms that riboflavin functions as a catalyst for redox reactions in numerous metabolic pathways and in energy production. The daily recommended allowance for riboflavin is 1.3 mg/day and 1.1 mg/day, for males and females, respectively. Due to its unquestionable importance in human nutrition, riboflavin was determined in the selected traditional foods analysed in the frame of the European Project BaSeFood (Sustainable exploitation of bioactive components from the Black Sea Area traditional foods). Riboflavin was determined according to the method EN 14152:2003. The sample is extracted after acid hydrolysis followed by dephosphorylation (with enzymatic treatment) and quantified by High Performance Liquid Chromatography with Fluorescence detection. The quantification limit of the method is <0.02 mg/100 g. This is an accredited method and the laboratory participates successfully in proficiency testing schemes. All the analyses were carried out protected from light because riboflavin is very sensitive to light. Analysis are being carried out in selected traditional foods from six Black Sea Area countries, which belong to the following groups: cereals and cereal based foods; vegetables; fruits; products from oilseeds; herbs, spices and aromatic plants; and fermented products. Our results show that 76.5 % of the analysed traditional foods had riboflavin content higher than 0.02 mg/100 g per edible portion. Roasted sunflower seeds presented the highest concentration of riboflavin (0.19 mg/100 g per edible portion). Therefore, traditional foods from Black Sea Area countries can give a good contribution to riboflavin dietary intake.